Model Integrasi Keilmuan Pesantren Pada Pendidikan Tinggi Keagamaan Islam Di Indonesia - Akhmad Shunhaji; Binti Khoiriyah (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
This qualitative research on scientific integration in the Islamic Religious Higher Education in Indonesia (PTKI) departs from the main question, what is the model of integration with pesantren scientists at PTKI? The choice of PTKI to be the focus of this study was determined based on a purposive sampling technique that aimed at three state Islamic universities, namely UIN Jakarta, UIN Malang and IAIN Tulungagung. Because it was conducted during a pandemic, this research is not a pure field study. This study draws information from the available data supported by semistructural interviews and sporadic observations. The main conclusion in this study is the variety of pesantren models applied in PTKI as a non-formal education system. Each campus has the autonomy to apply the pesantrenan education model. The concept of implementing Madrasah Diniyah takmiliyah Al-Jami'ah at the Ministry of Religion has not or has not even become a reference for the three PTKINs studied. The three PTKIN that are the focus of this research have the same name for the implementation of pesantrenan education, namely "Ma'had Al-Jami’ah". UIN Jakarta and UIN Malang emphasize the excellence of the boarding system so that it only accommodates hundreds of students in a very limited number compared to the ratio of the total number of UIN students of tens of thousands. Ma'had Al-Jami’ah at IAIN Tulungagung applies two models. The first is with a boarding system for around 200 new students. Second, there is a Diniyah Madrasah for all students, especially for semester 1 and 2 students, which is held before lecture activities by utilizing the campus building. Thus, students' access to pesantrenan education will be wider and unlimited. The level that is carried out is also tiered which is divided into two concentrations, each choice and level according to the abilities and interests of the students. Ma'had al-jami'ah in the three campuses studied, even at the highest level, is still below the ideal standard of the pesantren. Most of the material content is only the basic materials taught at the pesantren. So the hope of producing Islamic religious experts (ulama) through Ma'had al-jami'ah seems rather difficult to be realized, except for mahasantri who already have the scientific basis of the previous pesantren